The evasion in Engineering courses and their relationship with Mathematics: an analysis from COBENGE - Godoy, Elenilton Vieira; Almeida, Eustáquio de (Educação Matemática Debate, 2017)
This paper is part of the research line Elements and Mathematics Teaching Methodology and was aimed to analyze the articles on the teaching of mathematics and emphasize aspects related evasion in Engineering courses presented at the Brazilian Engineering Education Congress (COBENGE) in the period between years 2000 to 2014. The choice to analyze the work from the year 2000 is due mainly to the fact that at that time, the enrollment of higher education increased by over 150,0%. The methodological approach that supported the study was quantitative through content analysis, however, the immersion in COBENGE the work was given by a study on the state of the art. Research conducted showed that there is strong relationship between evasion and failure in the disciplines of basic cycle, especially the discipline of Differential and Integral Calculus.